Effectiveness of Digital Book-Based Discussions on Type 2 Diabetes Prevention in Obese-Risk Adolescents - Cahyati, Tasya Ingrit; Simbolon, Demsa; Sitompul, Linda (Jurnal Kesehatan Komunitas Indonesia, 2025)
Type 2 diabetes mellitus is a chronic disease characterized by elevated blood glucose levels due to insulin resistance. It is increasingly prevalent among adolescents as a result of unhealthy lifestyles and obesity. The prevalence of adolescent obesity in Bengkulu Province continues to rise, particularly in the service area of Lingkar Barat Public Health Center, which includes Public High School (SMAN) 7 Bengkulu City. This study aimed to determine the effectiveness of the discussion method using digital book media on type 2 diabetes mellitus prevention behaviors among adolescents at risk of obesity at SMAN 7, Bengkulu City. This quantitative research employed a quasi-experimental design with a pre-test and post-test with a control group approach. The sample comprised 37 respondents in the intervention group and 37 in the control group. Data were collected using questionnaires and analyzed using the Shapiro–Wilk test for normality, the Wilcoxon signed-rank test, and the Mann-Whitney U test. The study was conducted from March to April 2025. The Wilcoxon signed-rank test results in the intervention group showed a p-value of 0.000 (<0.05), indicating a significant change in the mean prevention behavior score before and after the intervention. Similar results were observed in the control group; however, the improvement in the intervention group was greater. The discussion method using digital book media effectively improved type 2 diabetes mellitus prevention behaviors among adolescents at risk of obesity.